2019
DOI: 10.1101/542720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationships between depressive symptoms and brain responses during emotional movie viewing emerge in adolescence

Abstract: Affective disorders such as major depression are common but serious illnesses characterized by altered processing of emotional information. Although the frequency and severity of depressive symptoms increase dramatically over the course of childhood and adolescence, much of our understanding of their neurobiological bases comes from work characterizing adults' responses to static emotional information. As a consequence, relationships between depressive brain phenotypes and naturalistic emotional processing, as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…Additionally, inclusion of a sample of children and adolescents specifically allows us to test if brain-behavior relationships look significantly different in development than they do in adulthood. Recent work found that a relationship between depression symptoms and intersubject correlation during movie watching emerges in adolescence, suggesting that brain-behavior relationships may vary as a function of age (Gruskin et al, 2020). Ultimately, across both the developmental and young adult sample, we find significant evidence for the AnnaK model.…”
supporting
confidence: 52%
“…Additionally, inclusion of a sample of children and adolescents specifically allows us to test if brain-behavior relationships look significantly different in development than they do in adulthood. Recent work found that a relationship between depression symptoms and intersubject correlation during movie watching emerges in adolescence, suggesting that brain-behavior relationships may vary as a function of age (Gruskin et al, 2020). Ultimately, across both the developmental and young adult sample, we find significant evidence for the AnnaK model.…”
supporting
confidence: 52%
“…Adolescence development tasks embody personal independence and a philosophy of life which are confronted with learning to achieve new forms of intimate relationships, preparing for an occupation, achieving emotional independence of parents, and developing a mature set of values and ethical principals (Ekerdt, 2002;Gruskin, Rosenberg, & Holmes, 2019). Therefore, adolescence can be defined as a period of experiment and exploration of various identities and attitudes which rapid change and is centered on adolescent's relationship to authority (Lawrence, 2006;Maes et.al., 2019).…”
Section: Introductionmentioning
confidence: 99%